Pathways and determinants of sustainable energy use for rice farms in India - Nayak, Harisankar; Parihar, Chiter Mal; Aravindakshan, S.; Silva, J. V.; Krupnik, Timothy J.; McDonald, Andrew J.; Kakraliya, S.; Sena, Dipaka Ranjan; Kumar, V.; Sherpa, S.; Bijarniya, D.; Singh, L. K.; et al. (Elsevier, 2023)
Rice cultivation in the Western Indo-Gangetic plains of India is often blamed for higher energy use. Thus, a bootstrapped meta-frontier approach with a truncated regression approach was used on a database of 3832 rice farms from the input-intensive rice production tracts of western Indo-Gangetic Plains for sustainable energy-use assessment. Farms were classified based on efficiency scores to screen the inefficient practices and farms in Indo-Gangetic Plains. The district-specific technical-efficiency scores ranged between 0.68 and 0.99, with a mean of 0.86–0.90, suggesting average improvement in energy-use efficiency by 10–14% within the district. The mean meta-frontier technical-efficiency score ranged between 0.60 and 0.81. On average, the energy-use-efficient farms had 42% or higher energy-use efficiency in the districts of Ambala, Fatehgarh Sahib, and Karnal. In contrast, in other districts, the efficient farms had 5-19% higher energy-use efficiency. There is evidence of a higher number of tillage, irrigation, and fertilizer application among the inefficient farmers, specific to some districts. The efficient as well as inefficient farmers in Kapurthala and Ludhiana spend similar energy in tillage, whereas, the energy output from both efficient and inefficient farms are similar in Kurukshetra. Thus, there is a need of differential attention specific to district and practices. The evidence provided in this study can help to identify pathways toward sustainable energy use for future rice production in other ecologies too. Similar type of analysis can be carried out for other parameters like profitability and carbon footprint to explore where farmers are spending extra monetary and carbon inputs, and not getting additional yield benefits.